Available studies fail to provide strong evidence of increased risk of diarrhea mortality due to measles in the period 4-26 weeks after measles rash onset - Bianca D. Jackson; Robert E. Black (BMC, 2017)
Abstract Background Measles vaccination effectiveness studies showed dramatic decreases in all-cause mortality in excess of what would be expected from the prevention of measles disease alone. This invited speculation that measles infection may increase the risk of diarrhea morbidity and mortality subsequent to the acute phase of the disease. The aim of the present systematic review is to summarize the existing evidence in the publically available literature pertaining to the putative causal link between measles and diarrhea in the period 4-26 weeks following measles rash onset. Methods We searched the PubMed, Embase, Open Grey and Grey Literature Report databases for relevant literature using broad search terms. Prospective, retrospective and case-control studies in low- and middle-income countries involving children under five wherein relevant evidence were presented were included. Data were extracted from the articles and summarized. Results Fifty abstracts retrieved through the database searches met the initial screening criteria. Twelve additional documents were identified by review of the references of the documents found in the initial searches. Six documents representing five unique studies that presented evidence relevant to the research question were found. Four of the included studies took place in Bangladesh. One of the included studies took place in Sudan. Some measles vaccine effectiveness studies show lower diarrhea morbidity and mortality among the vaccinated. However, children who received vaccine may have differed in important ways from children who did not, such as health service utilization. Additionally, cohort studies following unvaccinated children showed no difference in diarrhea morbidity and mortality between cases and controls more than 4 weeks after measles rash onset. One study showed some evidence that severe measles may predispose children to gastroenteritis, but was not able to show a corresponding increase in the risk of diarrhea mortality. Conclusions The available evidence suggests that the risk of measles-associated diarrhea mortality is largely limited to the 5-week period 1 week prior to and 4 weeks after measles rash onset, and that there is no increased risk of diarrhea mortality in the longer-term caused by measles.